Characters' Psychological Dimensions In Amro Abd Alhamid's Novel "Zicola's Land" (Journal of Namibian Studies : History Politics Culture, 2023)
Our research aims at studying the characters, according to a psychological perspective, since the character is the basic foundation of novel, because of the relationship between psychology and literature. Literary studies have significantly benefited from psychology results, especially from Segment Froid’s sayings, through the critical contextual method (psychological criticism), which looks on the novel characters’ psychology, feelings, emotions and relationships with familial and social environment for the sake of constructing novel and ideas. All the artistic elements, included within the novel, are linked to the character, and they’re performed through. The descriptive analytical method has been followed in defining psychological analysis, psychological criticism and the relationship between them. The psychological criticism method has been adopted in studying the novel through applying its concepts and procedures on characters. Concerning the study results, we’ve attained the fact that there’s a close relationship between psychology and literature, although psychology concepts and sayings can’t be totally applied on literature and its texts. The novelist has precisely chosen the characters whose roles and tasks are appropriate to their physical, moral and psychological specificities.